Qualitative Processes Associated with Social Interaction with ChatGPT and Digital Mental Health Literacy among Indonesian Generation Z - Igriya Fauzi Nabilah; Wihda Maulani; Amelia Putri Nirmala (Journal of Psychological Perspective, 2026)
The rapid adoption of generative artificial intelligence among Indonesian Generation Z has not been accompanied by adequate readiness to critically navigate the mental health information it provides. This study examined the association between Social Interaction with ChatGPT and Digital Mental Health Literacy (DMHL) and explored the qualitative processes that may help explain this association. It was hypothesized that social interaction with ChatGPT would be positively associated with digital mental health literacy. This study employed an explanatory sequential mixed-methods design. The quantitative phase involved 195 Indonesian Generation Z ChatGPT users aged 18–25 years and was analyzed using Pearson's and Spearman's correlation analyses, followed by simple linear regression. Subsequently, twelve participants were purposively selected to represent four qualitative sampling profiles: High–High, Medium–Medium, Low–Low, and High–Low. The quantitative findings revealed a significant positive relationship between social interaction with ChatGPT and digital mental health literacy (r = 0.660, R² = 0.435, p < .001). The qualitative findings suggested that the association may be expressed through different patterns of emotional accessibility, perceived relational closeness, critical awareness, reflective practice, and continued reliance on human support. The findings indicate that interaction with ChatGPT should be understood in relation to both users’ cognitive evaluation of information and their emotional and relational experiences, while maintaining appropriate human and professional support.